A betaine adduct of N-heterocyclic carbene and carbodiimide, an efficient ligand to produce ultra-small ruthenium nanoparticles1. Issue 22 (18th March 2015) - Martínez-Prieto, L. M.; Urbaneja, C.; Palma, P.; Cámpora, J.; Philippot, K.; Chaudret, B.
<x xml:space="preserve">Abstract</x> A betaine adduct (ICy·(p-tol)NCN) as an efficient ligand to prepare ultra-small (1–1.3 nm) ruthenium nanoparticles (RuNPs).